Darstellung der alpinen Landschaft in Outdoorberichten - Anna Woronina (Linguistische Treffen in Wrocław, 2021)
The outdoor report is a popular but no so deeply covered text type of journalistic style as well as of internet-based communication. Outdoor reports represent a hybrid genre that pursues the broad goal of making hiking as attractive as possible for the general public. As a hybrid text type, they deserve a special linguo-stylistic approach, because of their factual objectivity on the one hand and author- related aesthetic subjectivity on the other hand. Furthermore, these texts often have an interdiscursive or intermedial character. In this article, we will discuss the basics of text type theory and spatial theory based on W. Albert, Peter J. Brenner, Ju. Lotman, D. S. Likhatchov. This establishes the theoretical base- line of the following research. The research focuses on the characteristics of the geographically defined space of the Alpine region as well as text-forming spatial-related characteristics of the text type outdoor report. The aim is to show on the concrete contexts, how in outdoor reports the linguo-stylistic means of objective as well as subjective representation are used by the author to increase expressiveness and impact on the recipient. This is the original value of the analysis. This carried out analysis addresses the matter of classifying and interpretation methods, as well as basic principles of geopoetics approaches. In the process of analysis is inter alia elucidated, that the outdoor report of NZZ-column coevally exhibits particular poetic intentions and implicates using figures of speech as well as other connotative words and constructions. By means of the analysis, it is shown that various linguo-stylistic devices are used for creation of the Alpine space such as toponymes of different types, factual and expressive epithets, comparisons, which acts as text productive. The essential part is the representation of the charms of the Alpine landscape, which is reflected in symbolic subtext. As the analytic material consists of five outdoor reports from the Neue Zürcher Zeitung – from the section „Hiking in the Alps“ by Heinz Staffelbach from 2020.